Optical characterization of nano-pentacene thin films - Yahia, I. S.; Rammah, Y. S.; AlFaify, S.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
The optical properties of pentacene thin films prepared by thermal evaporation technique at room temperature are investigated. X-ray diffraction and atomic force microscopy on the samples showed the existence of the nanostructure in the evaporated pentacene films. Optical properties were studied for the pentacene thin films with various thicknesses (119, 225, 380, and 520 nm) at normal incidence of light in the wavelength range of 300-2600 nm. The refractive index n and the absorption index k were computed using the obtained data of transmittance T(lambda) and reflectance R(lambda). The complex dielectric constant, dissipation factor tan delta, optical conductivity sigma(opt), optical band gap E-g(opt), volume energy loss (VELE), and surface energy loss (SELF) functions were calculated and interpreted. The results of the optical absorption data showed that pentacene thin film has mainly three indirect energy gap bands in the energy range from 1.70 to 3.45 eV. The obtained results indicate that the pentacene organic semiconductor thin film is a good candidate in opto-electronic devices based on its band gap and dispersion parameters. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Organic semiconductor; Nano-crystalline pentacene; Thermal evaporation; XRD; Optical dispersion parameters; Optical constants; Optical conductivity